Melioidosis: Truly Uncommon or Uncommonly Diagnosed in Bangladesh? A CaseReport - Rahim, Muhammad Abdur; Afroze, Samira Rahat; Uddin, Khwaja Nazim; Barai, Lovely (BIRDEM Medical Journal, 2016)
Melioidosis is a rarely reported infectious disease in Bangladesh. Patients may present with fever, soft tissue infection, deep seated abscess, arthritis and septicaemia, specially if immunocompromised. It often mimics tuberculosis. Here we describe a case of melioidosis in a middle aged Bangladeshi diabetic farmer who presented with fever, soft tissue infection and septic arthritis involving right hip joint. Culture of pus from soft tissue infection and synovial fluid revealed growth of Burkholderia pseudomallei. He was treated with prolonged courses of antibiotics including ceftazidime in initial phase followed by co-trimoxazole and was cured completely. Birdem Med J 2015; 5(1) Supplement: 49-51